Abiunistration of Student Servos at the University of Science at Technology, Kumasi, Ghana. (Journal of Science and Technology, 2016)
This paper looks at the issue of student services at the University of Science and Technology (UST) at Kumasi, Ghana, It reviews the operation and administration of these services in relation to what pertains in American institutions of higher learning. The nature of these services and the calibre of personnel charged with this responsibility are all considered. The paper acknowledges the peculiarity of the situation at UST in relation to the provision of such services and the fact that student service personnel as a profession is yet to take roots at UST and Ghana, for that matter. This fact notwithstanding, the paper contends that with the increasing demands of today's college student development, the changes and reforms taking place in Ghana's tertiary educational system and the expectations of society of a purposeful education from educational institutions, it is about_ time the University considered a review of its "in loco parentis" relationship with its students and the corresponding form and administration of student services.